Disparities in Policies, Practices and Rates of Pediatric Kidney Transplantation in Europe. Issue 8 (29th May 2013) - Harambat, J.; van Stralen, K. J.; Schaefer, F.; Grenda, R.; Jankauskiene, A.; Kostic, M.; Macher, M.‐A.; Maxwell, H.; Puretic, Z.; Raes, A.; Rubik, J.; Sørensen, S. S.; et al.
Abstract: We aimed to provide an overview of kidney allocation policies related to children and pediatric kidney transplantation (KTx) practices and rates in Europe, and to study factors associated with KTx rates. A survey was distributed among renal registry representatives in 38 European countries. Additional data were obtained from the ESPN/ERA‐EDTA and ERA‐EDTA registries. Thirty‐two countries (84%) responded. The median incidence rate of pediatric KTx was 5.7 (range 0−13.5) per million children (pmc). A median proportion of 17% (interquartile range 2−29) of KTx was performed preemptively, while the median proportion of living donor KTx was 43% (interquartile range 10−52). The median percentage of children on renal replacement therapy (RRT) with a functioning graft was 62%. The level of pediatric prioritization was associated with a decreased waiting time for deceased donor KTx, an increased pediatric KTx rate, and a lower proportion of living donor KTx. The rates of pediatric KTx, distribution of donor source and time on waiting list vary considerably between European countries. The lack of harmonization in kidney allocation to children raises medical and ethical issues. Harmonization of pediatric allocation policies should be prioritized. Abstract : The results of this study, combining data from a European Registry with a survey of 38 European countries about allocation policies, practices, and rates of pediatric kidney transplantation, show that considerable disparity exists between countries.